Studies Directed Towards the Synthesis of Bryostatin: A Stereoselective Synthesis of the C7–C16 Fragment - Yadav, Jhillu S.; Aravind, Seema; Gundluru, Mahesh Kumar; Reddy, Basi V. Subba (Synthesis, 2012)
A stereocontrolled asymmetric synthesis of the C7–C16 fragment of bryostatins is described. The key steps involved were a Jacobsen’s hydrolytic kinetic resolution and a Reformatsky reaction to build the C11–C16 fragment. A vinyl Grignard reagent was used to construct the C7–C10 fragment. The C11–C16 and C7–C10 fragments were coupled by means of a cross-metathesis reaction to give a key intermediate. The pyran ring system was constructed by means of an oxa-Michael reaction.
Keywords: heterocycles; stereoselective synthesis; medicinal chemistry; pyrans